On The Performance of Expected Transmission Count (ETX) Metric In Flying Ad-Hoc Network. (Sebha University Conference Proceedings, 2025)
Flying Ad Hoc Network (FANET) is an innovative wireless communication framework that consist of the autonomous movement of Unmanned Aerial Vehicle (UAV) systems and allows communicate among them. A FANET offers an effective real-time communication solution for several applications such as commercial and civilian by treating each UAV as a router, which allow packets to be forward and receive. In contrast to Mobile Ad Hoc Networks (MANETs) and Vehicular Ad Hoc Networks (VANETs), FANETs, have a high speed mobility, irregular connectivity, and rapid changes in topology, which provide significant issues in the formulation of routing metrics. The Expected Transmission Count (ETX) is a routing metric designed to identify high-throughput pathways in multi-hop wireless networks. This study examines the effectiveness of the ETX metric in FANET, building on prior research that evaluated ETX across various multi-hop networks, including wireless mesh networks, to determine its viability as a primary routing metric or the need for enhancements. We use the NS-3 simulator to integrate the ETX metric with the Ad-hoc On-Demand Distance Vector (AODV) routing protocol. We have made simulation studies across several network sizes. The acquired data are compared with acquired data are compared of the hop count metric to assess its efficacy in the performance of FANETs. We use end-to-end delay, packet delivery ratio (PDR), useful traffic ratio (UTR), throughput, and jitter as keys performance metrics. The findings indicate that ETX outperforms hop count for PDR, UTR, and throughput, however, ETX exhibits an increased in delay and jitter relative to hop count. The results show that ETX may greatly improve the efficiency of routing in FANETs. This indicates that it may be a crucial factor in evolving new routing protocols for next-generation FANETs.